(untitled) (PANGEEA, 2025)
The paper analyzes the current state of the irrigation plots with the sprinkling watering regarding the hydraulic efficiency in the transport and distribution of water. Sprinkler irrigation plots have been in operation for about 35-40 years. They present phenomena of wear and aging of the structural components (pipes, fireplaces with hydraulic installations, hydrants, pumping stations, supply channels). Research conducted on a series of irrigation plots in the eastern and southern part of Romania, with various periods of exploitation, has highlighted the complexity of the degradation process of the structural elements. Degradation of the structural components of the irrigation plot causes the formation of water losses, which reduces the hydraulic efficiency. Research has shown the excessive degradation of the supply channels of the pumping stations. The pipes are worn, with cracks and cracks through which there is continuous water loss. Hydraulic installations in fireplaces and pumping stations are worn out and have high water losses. The use of European funds requires the presentation of measures regarding the reduction of water losses.